Sorption of Ga(III), Cu(II), Ni(II) and Zn(II) on Synthetic Polymeric Resins - Arifi, A.; Hanafi, H.A. (Asian Journal of Chemistry, 2010)
Poly(acrylamide-acrylic acid-dimethylaminoethylmethacrylate) [P(AM-AA-DMAEM)] and poly(acrylamide-acrylic acid)-ethylenediaminetetracetic acid disodium [P(AM-AA)-EDTANa2] were prepared by g radiation-induced template polymerization technique. The prepared polymeric materials were used for the sorption of Ga(III), Cu(II), Ni(II) and Zn(II) in aqueous solution. The effect of pH, weight of resins, metal ion concentrations and contact time on the sorption of these metal ions were studied.